(3EYdGe GdCYdGe ajef HhjY bHd GdGMJdGe ef edhc GdESdGe heG jJYdb HPdc ef GdcdGes - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi HQC GdNdb Ke jYjOg s
(3BNQgG (B:s
(3hcGfJ HjYI GdYGeI EjGg (B( (3jTjQ Edi YHO GdeDef (B) (3jhe GdLeYI s
(3GdehLhO efg GdbSe GdChd hGdKGfi hGdKGdK jfJgi Edi YHO GdeDef Hf Ydi NdjaI GdehMOjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B261 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B20 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdJjehQjI (B((3JGQjN (B1252) s
Keywords: (3GdJGQjNs